Evaluation of bone repair using chitosanhydroxyapatite biomaterial for Bone tissue engineering - Yadav, Namrata (IIT(BHU), Varanasi, 2019)
Today in Tissue Engineering has gained prominence in the modern research focussed in the conditions of trauma and injury.The bone-derived-osteoblast when seeded on scaffold material has displayed prominence in the treatment of the osseous medical condition. A promising route towards bone tissue engineering comprised of materials of the composite which can mimic properties of the extracellular matrix (ECM) components. The process development in designing of the cell-material construct to enable regeneration of bone is in increasing demand for the repair of defective and/or diseased bone tissue. With properties of constituents being attributed to both origin and chemical modifications, natural polymer-based, ‘polypeptide-polymer-ceramic-cell material’ shows significant role in bone tissue engineering.
This Thesis Submitted by IIT(BHU), Varanasi Phd scholar & Supervised by Prof. Pradeep Srivastava.
Keywords: bone repair; chitosanhydroxyapatite; biomaterial; Bone tissue